LILIS SURYANIâ€™S â€œGANG KELINCIâ€ AS A REFLECTION OF SOCIAL REALITIES IN INDONESIA (1957â€“1965) - CHRIS WOODRICH (Unipdu Jombang, 2013)
Chris Woodrich Universitas Gadjah Mada chris_woodrich@hotmail.com Â Abstract Music does not live in a vacuum. It is forever growing and mutating, at once reflecting and creating social realities in the culture which birthed it, be they historical developments or contemporary conditions. The song â€œGang Kelinciâ€, written by Titiek Puspa and sung by Lilis Suryani, provides an interesting case in point: its lyrics provide a stark portrayal of the suffering of the Indonesian lower class during the Guided Democracy period (1957â€“1965).This is only emphasised by its whimsical imagery and jaunty music, which was used to avoid censorship during the totalitarian Guided Democracy period. Key Words: gang kelinci, Lilis Suryani, Titiek Puspa Â Abstract Musik tidak berada dalam suatu vakum. Ia selalu berkembang dan berubah, mencerminkan dan menciptakan realitas sosial dalam budaya yang telah melahirkannya, baik perkembangan historis maupun keadaan kontemporer. Lagu â€œGang Kelinciâ€, yang ditulis oleh Titiek Puspa dan dinyanyikan Lilis Suryani, menjadi salah satu contoh yang menarik: lirik lagu ini menawarkan gambaran kesengsaraan yang dialami masyarakat kelas bawah Indonesia selama periode Demokrasi Terpimpin (1957â€“1965). Ini semakin ditekankan dengan pencitraannya yang fantastis dan musik yang gembira, yang digunakan untuk menghindari penyensoran dari pemerintah totaliter demokrasi terpimpin. Kata Kunci: gang kelinci, Lilis Suryani, Titiek Puspa